Urolithins: potential biomarkers of gut dysbiosis and disease stage in Parkinson's patients. Issue 11 (25th May 2022) - Romo-Vaquero, María; Fernández-Villalba, Emiliano; Gil-Martinez, Ana-Luisa; Cuenca-Bermejo, Lorena; Espín, Juan Carlos; Herrero, María Trinidad; Selma, María Victoria
Abstract : A gradual increase in urolithin non-producers (UM-0) concomitant with a decrease in urolithin producers (UM-A and UM-B) was observed as the disease severity increased in Parkinson's disease patients. Abstract : Gut microbiota alteration (gut dysbiosis) occurs during the onset and progression of Parkinson's disease. Gut dysbiosis biomarkers could be relevant to prodromal disease. Urolithins, anti-inflammatory metabolites produced from some dietary polyphenols by specific gut microbial ecologies (urolithin metabotypes), have been proposed as biomarkers of gut microbiota composition and functionality. However, this has not been explored in Parkinson's disease patients. The current study aimed to assess associations between urolithin metabotypes, gut dysbiosis and disease severity in Parkinson's disease patients. Participants (52 patients and 117 healthy controls) provided stool samples for microbiota sequencing and urine samples for urolithin profiling before and after consuming 30 g of walnuts for three days. Data on demographics, medication, disease duration and Hoehn and Yahr disease stage were collected. We observed a significant gradual increase of urolithin non-producers (metabotype-0) as the disease severity increased. The gut microbiome of metabotype-0 patients and patients with the greatest severity was characterized by a more altered bacterial composition, i.e., increased pro-inflammatory Enterobacteriaceae and reduced protective bacteria against autoimmune and inflammatory processes, including butyrate and urolithin-producing bacteria (Lachnospiraceae members and Gordonibacter ). Besides, their microbiome was characterized by predictive functions of lipopolysaccharide biosynthesis and metabolism of glutathione, cysteine and methionine that could indirectly reflect the gut pro-inflammatory status. Urolithin detection in urine is a feasible, non-invasive and fast approach that can reflect gut microbiome dysbiosis and intestinal inflammation in Parkinson's disease patients. Our current study could provide novel strategies for improving diagnostics, and for preventing and treating disease progression in microbiota-based interventions.